2015
DOI: 10.1007/s12192-015-0588-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-based HSP70 promoter-driven VEGFA induction by resveratrol promotes angiogenesis in a mouse model

Abstract: Several studies of stem cell-based gene therapy have indicated that long-lasting regeneration following vessel ischemia may be stimulated through VEGFA gene therapy and/or MSC transplantation for reduction of ischemic injury in limb ischemia and heart failure. The therapeutic potential of MSC transplantation can be further improved by genetically modifying MSCs with genes which enhance angiogenesis following ischemic injury. In the present study, we aimed to develop an approach in MSC-based therapy for repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The hepatocyte growth factor (HGF) shRNA clone (TRCN0000336131; GGTAAAGGAGGCAGCTATAAA) targeted at the mouse HGF transcript was purchased from the National RNAi Core Facility, Academia Sinica (Taipei, Taiwan, http://rnai.genmed.sinica.edu.tw). Lentiviral constructs were generated by using three packaging plasmids—pMDLg/pRRE, CMV‐VSVG, and RSV‐Rev—in 293T cells, as described by Chen et al []. MSCs were treated with viral supernatant and polybrene for 24 hours before selection with 0.5 μg/ml puromycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatocyte growth factor (HGF) shRNA clone (TRCN0000336131; GGTAAAGGAGGCAGCTATAAA) targeted at the mouse HGF transcript was purchased from the National RNAi Core Facility, Academia Sinica (Taipei, Taiwan, http://rnai.genmed.sinica.edu.tw). Lentiviral constructs were generated by using three packaging plasmids—pMDLg/pRRE, CMV‐VSVG, and RSV‐Rev—in 293T cells, as described by Chen et al []. MSCs were treated with viral supernatant and polybrene for 24 hours before selection with 0.5 μg/ml puromycin.…”
Section: Methodsmentioning
confidence: 99%
“…tw). Lentiviral constructs were generated by using three packaging plasmids-pMDLg/pRRE, CMV-VSVG, and RSV-Rev-in 293T cells, as described by Chen et al [19]. MSCs were treated with viral supernatant and polybrene for 24 hours before selection with 0.5 mg/ml puromycin.…”
Section: Shrna Transductionmentioning
confidence: 99%
“…There are two other potential mechanims by which resveratrol acts: (i) by altering gut microbiota that have a role in several diseases and (ii) influencing stem cell proliferation and differentiation (52)(53)(54)(55).…”
Section: Resveratrol Is Cytoprotective In Naturementioning
confidence: 99%
“…As a protective response to external stimuli, Hsps increase their expression, help to maintain the metabolic and structural integrity of the cells, and enable the cells to become more resistant to stress conditions [ 32 34 ]. It is also suggested that Hsps inhibit apoptotic cell death [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that Hsps inhibit apoptotic cell death [ 32 ]. Hsp70 [ 33 ] and Hsp90 [ 34 ] in combination or alone play a major role in morphogenesis and dimorphism [ 35 ]. Protein denaturation has been reported in stress conditions and during modulation in temperature, which causes native misfolded aggregation of proteins that ultimately leads to the loss of biological functions as well as apoptosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%